Pelatihan Penulisan Artikel Ilmiah Bagi Guru SMAN 15 Kabupaten Bone - Asmunandar Asmunandar; Andika Wahyudi Gani; Dyan Paramitha Darmayanti; Darman Manda; Andi Sadriani (Panrita Inovasi: Jurnal Pengabdian Kepada Masyarakat, 2022)
To improve student achievement, teachers must innovate in learning. This ensures that students learn at their best, both independently and in the classroom. Learning model innovation is very necessary and very urgent, especially in the development of new learning models that can lead to better learning outcomes and increase efficiency and effectiveness. In addition, teachers must develop their potential in various ways. One of them is improving the ability to write scientific papers. By conducting article writing training, teachers are expected to have dual roles as practitioners and researchers. Therefore, teachers must conduct research to solve problems that arise in class and to serve as material for promotion. The Scientific Article Writing Training for Teachers of SMA Negeri 15 Bone, Bone Regency, was carried out in Bone Regency with the target of this activity being the teachers at the school. This activity is in the form of training with an emphasis on mastery of article writing.